Transforming Management Education: Integrating Sensorial, Emotional, and Spiritual Skills to Navigate Complexity - Ludviga, Iveta; Trenvouez, Arnaud; Karhu, Hanna; Eskola, Anne; Firescu, Violeta; Sava, Adriana; Leen, Elaine; Goubier, Vincent; Pons, Christophe; Sluka, Inese; Kakko, Anneli (Journal of Ecohumanism, 2025)
Higher education (HE) institutions and educators continually explore novel and practical pedagogical approaches to equip future managers with the skills to make effective decisions and navigate complex organizational environments. This paper presents an empirical case of a pioneering project that devised an innovative training methodology strategically using Sensorial, Emotional, and Spiritual (SES) skills, in addition to rational capacities, to address complex management cases. The methodology, rigorously tested over three years with students from four European universities, has demonstrated its potential to revolutionize management education and instilled confidence in its effectiveness. The results underscore the significant value of sensorial, emotional, and spiritual (SES) training within HE institutions. This training enhances the competencies necessary for future managers to tackle and resolve complex problems effectively, strengthening their ability to manage complex environments. The survey data and interviews we conducted indicate that sensory, emotional, and spiritual skills training has not only improved the competencies needed to manage complexity – awareness, sense of community, self and other regulation, and sense of life but has also transformed the students' approach to problem-solving. This transformative approach not only inspires hope for the future of management education but also suggests a potential for positive change. Our investigation presents Sensorial, Emotional, and Spiritual skills as a transformative subset of soft skills, advocating for the need for SES skills training for future managers. We discuss the implications for pedagogies and strongly advocate for including SES skills development in students’ training and learning at higher education institutions.